Ett vattendrags väg genom tid och landskap - Peterson, Ylva (2009)
Water is a vital element and also enriches the experience of landscapes. It is naturally in constant movement and change but also exposed to the hands of man. In this paper two stretches of water is described through landscape and time in correlation between development and the experience of the watercourse Höje-å in the rural parts of southern Sweden. The intention is to investigate how Höje-å has changed over time and also how it is experienced in the surrounding landscape. With the help of literary studies the history of Höje-å have been described and through the course of field-studies the experience of two different areas along the watercourse.